Light and pH Dual‐Degradable Triblock Copolymer Micelles for Controlled Intracellular Drug Release. Issue 15 (22nd May 2014) - Jin, Qiao; Cai, Tongjiang; Han, Haijie; Wang, Haibo; Wang, Yin; Ji, Jian
<x xml:space="preserve">Abstract</x> A novel amphiphilic ABA‐type triblock copolymer poly(ethylene glycol)‐b‐poly(ethanedithiol‐alt‐nitrobenzyl)‐b‐poly(ethylene glycol) (PEG‐b‐PEDNB‐b‐PEG) is successfully prepared by sequential thiol‐acrylate Michael addition polymerization in one pot. PEG‐b‐PEDNB‐b‐PEG is designed to have light‐cleavable o‐nitrobenzyl linkages and acid‐labile β‐thiopropionate linkages positioned repeatedly in the main chain of the hydrophobic block. The light and pH dual degradation of PEG‐b‐PEDNB‐b‐PEG is traced by gel permeation chromatography (GPC). Such triblock copolymer can self‐assemble into micelles, which can be used to encapsulate anticancer drug doxorubicin (DOX). Because of the different degradation chemistry of o‐nitrobenzyl linkages and β‐thiopropionate linkages, DOX can be released from the micelles by two different manners, i.e., light‐induced rapid burst release and pH‐induced slow sustained release. Confocal laser scanning microscopy (CLSM) results indicated that DOX‐loaded micelles exhibited faster drug release in A549 cells after UV irradiation. Furthermore, 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) results show that the DOX‐loaded micelles under UV light degradation exhibit better anticancer activity against A549 cells than that of the nonirradiated ones. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>